Endoscopic Sclerotherapy and Band Ligation in Secondary Prophylaxis of Esophageal Variceal Treatment - Catharina Triwikatmani; Putut Bayupurnama; Sutanto Maduseno; Neneng Ratnasari; Fahmi Indrarti; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Variceal bleeding is the most severe outcome of portal hypertension. Endoscopic sclerotherapy and band ligation are endoscopic treatment modalities for both active variceal bleeding and secondary prophylaxis. Endoscopic sclerotherapy has been carried out in Sardjito hospital since 1998, while band ligation has only been carried out since 2007 year. The aim of this study was to evaluate the long-term Result of endoscopic sclerotherapy and endoscopic band ligation in secondary prophylaxis of esophageal variceal eradication. Method: This is not a prospective study and is not randomized. The Results of patients who underwent endoscopic sclerotherapy and endoscopic band ligation from July 2003 to June 2009 were compared. Patients were evaluated for re-bleeding and recurrence rates. Results: Two hundred and seventy seven patients underwent endoscopic sclerotherapy and endoscopic band ligation during the period. One hundred and nine patients with varices eradication data; 49 patients who underwent sclerotherapy and 60 patients who underwent band ligation were followed for 1-119 (15.54 ± 20.70) months. The numbers of sessions for eradication were 4.33 ± 1.16 and 2.23 ± 0.59 for endoscopic sclerotherapy and endoscopic band ligation respectively (p 0.001). Re-bleeding and recurrence rates were 38.64% and 84.21% for endoscopic sclerotherapy, and 25.93% and 70% for endoscopic band ligation (p 0.05). Conclusion: Endoscopic band ligation is more effective than sclerotherapy in the eradication of esophageal varices.   Keywords: esophageal varices, sclerotherapy, band ligation, secondary prophylaxis